2017
DOI: 10.1080/10538712.2017.1393479
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study Perspective: The Experiences of Young Persons Testifying to Child Sexual Exploitation in British Criminal Court

Abstract: Three young persons who gave evidence about child sexual exploitation in criminal court using various testimonial supports were interviewed about their testimony experiences. The witnesses reported that they felt extreme pressure to remember events accurately and cared greatly about being believed. None reported their own coping strategies to alleviate stress and took comfort breaks only after they cried on the stand. Defense attorney questions were reportedly repetitive, rapid, confusing, and focused on secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…An additional central context in which children reported feeling unsafe, intimidated, and in need of protection during the legal process was in relation to any encounter that required them to face the perpetrator (Ahern et al, 2018; Collings, 2011; Connon et al, 2011; Hobbs et al, 2014; Peterson et al, 2019; Randell et al, 2018). Collings (2011) determined that the participating children did not experience being present in court as an outright negative experience, rather, it was seeing the perpetrator that they acknowledged as negative.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional central context in which children reported feeling unsafe, intimidated, and in need of protection during the legal process was in relation to any encounter that required them to face the perpetrator (Ahern et al, 2018; Collings, 2011; Connon et al, 2011; Hobbs et al, 2014; Peterson et al, 2019; Randell et al, 2018). Collings (2011) determined that the participating children did not experience being present in court as an outright negative experience, rather, it was seeing the perpetrator that they acknowledged as negative.…”
Section: Methodsmentioning
confidence: 99%
“…In Sumalla and Hernandez-Hidalgo's (2018) study, the need for support was related to the needs we found in our review: the need to be cared for, protected and informed. Both Ahern et al (2018) and Randell et al (2018) mentioned the lack of long-term stable support from professionals. Ahern et al (2018) added that many children did not know whom they could consult during the legal process.…”
Section: Thematic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The irony of a testimonial aid hampering the re-clarification of events is not evident in past research. Past scholars have found in investigative settings with past witnesses that the video-recorded statement has helped them recall certain details of events that helped to mitigate their fears of omission and consequently to seem less credible (Ahern, Kowalski, & Lamb, 2018). Reports of outcomes of technical difficulties in past research stem from the use of CCTV for the following reasons: such as an image and sound lag, focusing the camera on the accused, failure to set it up appropriately due to lack of training of courtroom staff, or that the technology was not available (Hickey & McDonald, 2018).…”
Section: Video-recorded Evidence: Can You Hear Me Now?mentioning
confidence: 99%
“…Furthermore, from the perspective of adjudicators, some prefer not to apply for the use of CCTV at all. Some witnesses have also reported how using testimonial aids may give them the appearance of being 'weak' in front of the offender and the court (Ahern, Kowalski, & Lamb, 2018). Some defence counsels have gone as far as to say that they dislike the use of testimonial aids such as screens and CCTV as it creates a barrier for them to discern whether or not children are lying or that not facing the accused makes it easier for them to lie (Bala, 2001).…”
Section: Video-recorded Evidence: Can You Hear Me Now?mentioning
confidence: 99%